The Value of the Revolving Door: Political Appointees and the Stock Market - Christoph Moser; Simon Lüchinger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We analyze stock market reactions to announcements of political appointments from the private sector and corporate appointments of former government officials. Using unique data on corporate affiliations and announcements of all Senate-confirmed U.S. Defense Department appointees of six administrations, we find positive abnormal returns for political appointments. These estimates are not driven by important observations, volatile stocks, industry-wide developments or the omission of further commonly used return predictors. Placebo events for close competitors and alternative dates yield no effects. Effects are larger for top government positions and less anticipated announcements. We also find positive abnormal returns for corporate appointments and positive effects of political connections on procurement volume. Our results suggest that concerns over conflicts of interest created by the revolving door are not unfounded, even in a country with strong institutions.
Keywords: G14; D73; G30; 330